EVALUASI PEMBELAJARAN DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Filza Zatalina Sofiyan; An Nida Sulistiana; Muhammad Raihan; Saefudin Zuhri; Wahyu Hidayat (Cahaya Ilmu Bangsa Institute, 2024)
This article discusses the importance of learning evaluation in education, particularly its role in assessing students' achievement of learning objectives and providing feedback to improve teaching methods. Evaluation allows educators to understand whether the teaching process is effective and helps students comprehend the material and achieve desired competencies. Additionally, evaluation identifies strengths and weaknesses in the learning process, enabling improvements and adjustments in teaching strategies. The article also explores the Islamic perspective on education, emphasizing the importance of evaluation as demonstrated in the Qur'an and Hadith, which highlight its role in assessing knowledge and moral behavior. The research uses a qualitative method, specifically library research, to review various literatures and theories related to educational evaluation. Key findings suggest that evaluation in education is not only a tool for assessing cognitive, affective, and psychomotor aspects but also plays a vital role in shaping students' spiritual and moral growth. The article concludes that evaluation, as outlined in both Islamic teachings and educational theories, is crucial for enhancing learning outcomes and improving teaching practices.